Estudo do rendimento de engenho das cultivares 409, PUITÁ e GURI de arroz em secador piloto a 40°C - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Rice is among the most produced and consumed grains in the world, for both the product and by-products are used commercially. In the agro-industrial processing has several factors that affect the final product quality and a key is drying because when done improperly favors the appearance of cracks in the grain, which determines the loss of commercial value of the grain, in addition to promoting Grain degradation. The objective of this study will indicate among cultivars 409, 424 and 417 which has better milling yield, the amount of whole grain, the comparative performed before and after drying and monitoring of grain moisture at 40 ° C pilot dryer. The work will be developed in the Company Fumacense in Alegrete, RS and will be used a randomized block design with treatments represented by cultivars with four replications. This determination is performed on two different days to three weeks, a total of 72 experimental units. The cultivars showed no significant difference in the yield of whole grains when compared, but it was noticed that when the ambient temperature was more pleasant, for the grain mass to reach 11.5% moisture, the time required was greater.
Keywords: Engenharia agrícola; Arroz; Arroz – Secagem; Arroz – Variedades; Oryza sativa; Agricultura - Estimativa de rendimento; Agricultural engineering; Agricultural estimating and reporting; Rice - Varieties; Rice; Rice - Drying; CNPQ::CIENCIAS AGRARIAS